Asymmetrical intersection between the middle cerebral artery and rhinal vein suggests asymmetrical gustatory cortex location in rodent hemispheres. (4th March 2015) - Kida, Ikuhiro; Enmi, Jun-ichiro; Iida, Hidehiro; Yoshioka, Yoshichika
Highlights: The rodent gustatory cortex is located near the intersection of the MCA and RHV. We investigated the location of the MCA and RHV intersection in both hemispheres. The MCA–RHV intersection is more anterior in the left hemisphere. The rodent gustatory cortex is asymmetrically located in the insular cortices. This landmark location needs to be verified for functional representation. Abstract: The rodent gustatory cortex is located in the anterior part of the insular cortex, which is near the dorsal part of the rhinal vein (RHV) and the intersection of the anterior and posterior regions of the middle cerebral artery (MCA). Thus, the intersection between the RHV and MCA is used as a landmark for the rodent gustatory cortex. In our previous study, we employed functional magnetic resonance imaging (MRI) to demonstrate that tastants evoked bilateral responses in the rodent insular cortices, but that these representations were asymmetrical between the hemispheres. In the present study, to clarify the observed asymmetrical responses, we performed magnetic resonance angiography in a 7.0-Tesla MRI scanner to determine the anatomical position of the rodent gustatory cortex, which was identified using the intersection of the MCA and RHV. We successfully observed the intersection while administering carbogen as an inhaled gas and found that the intersection in the left hemisphere is more anterior compared to that in the right hemisphere. Taken together with the previous functional MRI results, this result indicates that the gustatory representation in relation to the intersection may be identically conserved in the insular cortex of both hemispheres; therefore, the rodent gustatory cortex may be asymmetrically located between the left and right hemispheres. The result also suggests that this landmark location needs to be verified when investigating gustatory representations and responses.